Intervenção fisioterapêutica intraparto e sua repercussão nas variáveis obstétricas e neonatais: um estudo transversal - Melo, Jordânia Abreu Lima de (2021)
Introduction: The scope of scientific evidence supporting physical therapy intervention in obstetric care is still incipient in the literature. Objective: The dissertation comprises two studies, the first aimed to compare the obstetric outcomes of women undergoing physical therapy during labor (PT) with those who did not receive such assistance and to associate nonpharmacological methods (NFM) with the phases of TP; and the second was to verify the relationship between intrapartum physical therapy, perineal trauma, obstetric and neonatal variables. Methods: Cross-sectional analytical observational study, carried out at the Ana Bezerra University Hospital (HUAB), Santa Cruz, Rio Grande do Norte, Brazil, with parturient women aged between 18 and 40 years, with varying degrees of parity, single fetus and gestational age between 37 and 42 weeks of gestation. In the first article, data from 118 women were collected, the dependent variables were duration of labor and the expulsion period, and the independent variables were intrapartum physical therapy resources. The Kruskal-Wallis and Mann-Whitney tests were used to compare the observed obstetric results. In the second study, data were collected from 171 women, the dependent variable was perineal trauma (episiotomy and spontaneous perineal lacerations) and the independent variables were: intrapartum physical therapy intervention, physical therapy resources, obstetric, sociodemographic and neonatal variables. A bivariate analysis (chi-square) was performed between the dependent and independent variables, and Binary Logistic Regression was applied to verify whether the independent variables would be predictors of perineal trauma. For all analyses, a significance level of p<0.05 was adopted. Results: When comparing the obstetric outcomes of women undergoing physical therapy during RT with those who did not receive such assistance, it was observed that there were no statistically significant differences regarding the duration of RT and expulsion period between the groups with physical therapy monitoring and without this assistance, in the active (p=0.14) and latent (p=0.80) phases. However, there was a higher frequency of application of MNF by women accompanied by physical therapists. When the relationship between intrapartum physical therapy, perineal trauma, obstetric and neonatal variables was verified, a significant association was observed between perineal trauma versus: slow and deep breathing in the expulsive period (p=0.026), previous pregnancies (p=0.001) and number of vaginal deliveries (PV) (p=0.001). In the multivariate analysis, a 59.8% decrease in perineal trauma was observed (OR: 0.402 95%CI: 0.164; 0.982) in women who received respiratory guidance during the expulsion period by physical therapists, whereas women with up to two PV have 5 .38 (OR: 5.380 95%CI: 1.817; 15.926) times more likely to have perineal trauma when compared to those with more than two PV. Conclusion: The results of this study suggest that parturients accompanied by physical therapists during PD had more access to nonpharmacological resources and that breathing techniques guided by these professionals during the expulsion period seem to have a positive impact on the pelvic floor of low-risk or usual-risk parturients.